The demixing phase instability in the ion-dipole mixture - Chen, X.S.; Forstmann, F. (Condensed Matter Physics, 2001)
By considering the variation of the grand potential functional Ω with respect to small density fluctuations δρα(1) we can determine the phase instability of a system from the correlation functions. Using the reference hypernetted chain (RHNC) approximation the correlation functions of an iondipole mixture have been calculated. With the obtained correlation functions the phase behaviour of ion-dipole mixtures has been investigated. Розглядаючи варіацію функціоналу великого потенціалу Ω по відношенню до малих флуктуацій густини δρα (1), ми можемо визначити фазову нестійкість системи з кореляційних функцій. Обчислено кореляційні функції іонно-дипольної суміші, використовуючи базисне гіперланцюгове наближення. На основі отриманих кореляційних функцій була досліджена фазова поведінка іонно-дипольних сумішей.